Towns in the policy of the government of the Kingdom of Poland in 1815–1830 - Kania, Rafał (The Opole Studies in Administration and Law, 2019)
Cities and towns are of greater significance than a mere form of urbanization. They are centres of development and progress, accumulating the potential of industry and culture. The 19th century was the period of a dynamic development of cities and towns in Europe. It also saw flourishing of the middle-class and maturing of their views and system of values. Those processes involved towns on the territory of the Commonwealth of Poland, although on a very limited scale. This was a consequence of the exceptional situation after the Third Partition in 1795. The article analyses the position of towns in the policy of the government of the Kingdom of Poland (1815–1830).